Characterization of mannanase-producing bacteria from sago hump - Sri Wahyuni; Andi Khaeruni R; Lianto Lianto; Sidarmin Sidarmin; Holilah Holilah; Wahyu Prasetyo Utomo; Asranudin Asranudin (Waste Technology, 2016)
Sago is a hardwood that can be used as source of fiber hemicellulose mannan. The abundance of mannanase waste is potential for the production of functional foods such as Manno oligosaccharides. Sago hump which is sago processing waste is very potential for growth of microorganisms because it contains lignin, cellulose, starch, minerals and vitamins that can be used as sources of carbon and energy for the growth. In this study, BLS.11-01 and BLS.11-02 isolates have been isolated and characterized from waste of sago hump. Locust bean gum was used as  substrate for measuring the activity of mannanase. Both isolates had optimum temperatures at 70°C and 60°C while they remain stable at temperature range of 30°C - 90°C. Mannanase from BLS.11-01 and BLS.11-02 had optimum pH at 6 and 7, respectively, and were also stable in wide pH range of 2-8. Co2+ was a mannanase activator for both isolates. Cu2+, Zn2+, Ni2+, Ca2+ and Fe2+ were  mannanase inhibitors for two isolates. Tween 20 (0.5% and 1.0%) and NaCl (0.5% and 1.0%) were chemical reagents that could enhance the activity of BLS.11-01 and BLS.11-02 mannanase isolates.  While tween 80 (0.5% and 1.0%), urea (0.5% and 1.0%) and SDS (0.5% and 1.0%) were chemical reagents that were not effective for both isolates mannanase activity